Induced seismicity associated with fluid injection into a deep well in Youngstown, Ohio - Kim, Won-Young (Journal of geophysical research. Solid earth, 2013)
Over 109 small earthquakes (Mw 0.4–3.9) were detected during January 2011 to February 2012 in the Youngstown, Ohio area, where there were no known earthquakes in the past. These shocks were close to a deep fluid injection well. The 14 month seismicity included six felt earthquakes and culminated with a Mw 3.9 shock on 31 December 2011. Among the 109 shocks, 12 events greater than Mw 1.8 were detected by regional network and accurately relocated, whereas 97 small earthquakes (0.4 < Mw < 1.8) were detected by the waveform correlation detector. Accurately located earthquakes were along a subsurface fault trending ENE‐WSW—consistent with the focal mechanism of the main shock and occurred at depths 3.5–4.0 km in the Precambrian basement. We conclude that the recent earthquakes in Youngstown, Ohio were induced by the fluid injection at a deep injection well due to increased pore pressure along the preexisting subsurface faults located close to the wellbore. We found that the seismicity initiated at the eastern end of the subsurface fault—close to the injection point, and migrated toward the west—away from the wellbore, indicating that the expanding high fluid pressure front increased the pore pressure along its path and progressively triggered the earthquakes. We observe that several periods of quiescence of seismicity follow the minima in injection volumes and pressure, which may indicate that the earthquakes were directly caused by the pressure buildup and stopped when pressure dropped. Key Points 109 small potentially induced earthquakes occurred in Youngstown Ohio in 2011 Expanding high fluid pressure front progressively triggered the earthquakes Minima in injection pressure correlate with the quiescense of earthquake